Analysis of the Need for Development of Science Learning Tools Based on Religious Moderation in Junior High Schools in Conflict Prone Areas in West Nusa Tenggara - Yusuf; Badrun; Suhirman; Galuh Elisa Roliana Fatimah (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted to analyze the need for developing learning tools based on religious moderation in schools in conflict-prone areas in West Nusa Tenggara. This qualitative research uses a document analysis and narrative analysis approach. The research subjects were 20 people from conflict-prone areas in West Nusa Tenggara who were taken using a purposive sampling technique. Data was collected using documentation techniques, focus group discussions and in-depth interviews. Data from document analysis was interpreted using the thematic analysis method and FGD data was analyzed using narrative analysis to obtain conclusions regarding the need for developing learning tools based on religious moderation in schools in conflict-prone areas. The research results show that science learning tools in junior high schools in conflict-prone areas do not fully contain the value of religious moderation. Science learning tools for students in conflict-prone areas require explicit elements of moderation. Elements of religious moderation are needed in learning planning documents and textbook documents. The learning planning needed creates an inclusive learning environment, encourages cooperation, develops character values, increases religious understanding, and strengthens student character formation. The required teaching materials contain descriptions that provide a broad understanding of moderation, promote spiritual values, and assist students in character development.